An analytical framework to examine shari’ah-compliant mortgage financing by financial cooperatives in Malaysia - Zabri, Zaidi; Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar (IIUM Institute of Islamic Banking and Finance, 2015)
This paper utilises an analytical framework to explore and critically examine issues and challenges of offering Shari’ah-compliant mortgage financing by financial cooperatives in Malaysia. Concepts from five distinct theories (Theory of Credit Cooperative, Transaction Costs Theory, Agency Theory, Stakeholder Theory, and Theory of Credit Rationing) are modified and integrated to form a hybrid, layered framework. This is then used as a ‘lens’ to highlight the issues pertaining to business models and strategies, good governance, regulation and supervision, risk management, human resource management, which may influence the success of mortgage financing. This analytical framework is useful for relevant stakeholders on how to manage the issues, challenges, and harnessing the prospects of Shari’ah-compliant mortgage financing products. © 2015 The IIUM Institute of Islamic Banking and Finance.